Peran Self Compassion dalam Memoderasi Hubungan antara Motivasi Berprestasi dan Perfeksionisme pada Remaja SMAN Siwalima Ambon Boarding School - Azmi Nabila Djaman; Michael Yulian Feno; Agus Salim (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Adolescents studying at SMAN Siwalima Ambon demonstrate distinctive developmental characteristics shaped by a boarding school education system and the school’s status as an elite institution with high academic and non-academic expectations. These conditions foster strong achievement motivation and competitiveness, while simultaneously increasing vulnerability to perfectionistic tendencies. Although adaptive perfectionism may support high achievement, maladaptive perfectionism is often associated with psychological stress, excessive self-criticism, and emotional difficulties. In this context, self-compassion is considered an important psychological resource that enables adolescents to respond more adaptively to failure and pressure. This study aimed to explore the moderating role of self-compassion in the relationship between achievement motivation and perfectionism among adolescents at SMAN Siwalima Ambon. A quantitative correlational design was employed. The participants consisted of 161 students aged 15 to 21 years. Data were collected using the M-CUP Scale to measure perfectionism (Î± = 0.90), the Achievement Motivation Scale (Î± = 0.860), and the Self-Compassion Scale (Î± = 0.872). Data analysis was conducted using moderated regression analysis. The results indicated that achievement motivation and self-compassion each had a significant negative effect on perfectionism. However, theU) relating to perfectionism. These findings suggest that self-compassion and achievement motivation independently contribute to lower levels of perfectionism among adolescents. The results highlight the importance of developing school-based psychological interventions and guidance programs that promote self-compassion and adaptive achievement motivation to support students’ well-being in high-demand educational settings.